N-3 polyunsaturated fatty acids differentially enhance B-cell mediated immunity in lean and obese mice - Teague, Heather L. (East Carolina University, 2014)
Docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are bioactive n-3 polyunsaturated fatty acids (PUFAs) in fish oil that exert immunomodulatory effects. The general paradigm suggests n-3 PUFAs exert immunosuppressive effects, however, the role of n-3 PUFAs on B-cell mediated immunity is understudied. We first tested the hypothesis that n-3 PUFAs would suppress B-cell activation and antigen presentation. The functional changes n-3 PUFAs exert on B cells were determined and compared to dendritic cells (DC). Initially, we established n-3 PUFAs increased cytokine production from lipopolysaccharide (LPS) stimulated B cells ex vivo relative to the control. In contrast, n-3 PUFAs decreased DC activation with LPS by reducing cytokine secretion and decreasing surface expression of costimulatory molecules. The antigen presentation assays revealed n-3 PUFAs decreased IL-2 secretion from CD4 p+ T cells when B cells presented antigen compared to the control. In comparison, only CD69 surface expression on CD4 p+ T cells decreased when n-3 PUFA treated DCs presented the antigen compared to the control. Mechanistically, we investigated changes in lipid microdomain clustering on B cells and DCs induced by n-3 PUFAs to determine if the observed functional changes correlated with membrane changes. N-3 PUFAs diminished lipid microdomain clustering on the B-cell surface, but had no effect on DCs. We then relied on a lean and obese murine model to determine if the functional enhancement of B cells observed ex vivo were recapitulated in vivo. N-3 PUFAs increased serum IgM levels compared to controls when stimulated by a T-independent antigen. Additionally, n-3 PUFAs supplemented to an obesogenic diet rescued the decrement in serum IgM levels observed with the obesogenic diet compared to the lean control. Considering the limitations of fish oil, we investigated the effects of the clinically relevant EPA and DHA ethyl esters on antibody production in an obese murine model. EPA and DHA differentially increased ex vivo B-cell activation, in vivo natural serum IgM and cecal IgA compared to controls. Altogether, the data show n-3 PUFAs boost immune responses from B cells, which challenges the current notion about n-3 PUFAs, and has clinical implications for immunocompromised populations, such as the obese.
Keywords: Chemistry, Biochemistry; B cells; Docosahexaenoic Acids; Eicosapentaenoic Acid; High fat diet; Immunity; N-3 polyunsaturated fatty acids; Biochemistry; Obesity--metabolism; Biological Markers; Antigens, Differentiation, T-Lymphocyte--physiology; Fatty Acids, Omega-3--metabolism